Rain Park Designation as an Environmental Educational Tourism in aims of River Arrangement of Badung River, in Denpasar City - Purnaya, I Gusti Ketut; Laba, I Nengah; Semara, I Made Trisna; Tunjungsari, Komang Ratih (Journal of Business on Hospitality and Tourism, 2018)
This research was in purpose of conserving river environment in developing sustainable tourism by empowering local community to control balance or harmony in life depends on local genius. Heterogeneous tourism potentials owned by Badung river’s area to be enhanced as new attraction, within eco tourism concept. This research designated by using descriptive research, since authors explored data and information regarding topics to get in-depth data for further research. In this research, authors wanted to identify designation of rain park in order to arrange Badung river as an environmental educational tourism region. Data were collected through observations, documentation, and interview with qualitative descriptive as analysis technic. The result of the research showed the development of alternative tourist attraction, namely Rain Park in Badung’s River. This tourist attraction is a part of community-based tourism that utilize element of rain and water as an attraction. Moreover, this attraction will be a viable and possible option to answer any water pollution issue among Badung river area.